Characterization of the colloidal products of pentacarbonyliron oxidation - Jafelicci Júnior, Miguel [UNESP]; Conforto, Egle; Galembeck, Fernando (Elsevier, 1987)
Pentacarbonyliron was oxidized with H2O2, in organic solvents, to give colloidal sols. The aqueous-ethanolic sol is highly stable and undergoes thermally-reversible coagulation. Its solid phase was found to be a non-crystalline Fe (III) hydroxoacetate which is transformed to α-Fe2O3 when heated to 300°C. Iron-bound acetate groups are assumed to have a major role in the sol stability, by preserving the amorphous solid phase. Dry hydroxoacetate particles were heated under vacuum; scanning electron microscopy revealed that these particles coalesce and grow, as in a sintering process but at low temperatures (100-250°). © 1987.
Keywords: INORGANIC COMPOUNDS - Oxidation; SOLIDS - Microscopic Examination; SOLVENTS; HYDROXOACETATE PARTICLES; IRON HYDROUS OXIDE; PENTACARBONYLIRON OXIDATION; COLLOIDS